The Basic vs. Ability-to-Pay Approach: Evidence From China's Critical Illness Insurance on Whether Different Measurements of Catastrophic Health Expenditure Matter - Ying Zhang; Yongmei Guan; Ding Hu; Jacques Vanneste; Dongmei Zhu (Frontiers in Public Health, 2021)
Alleviating catastrophic health expenditure (CHE) is one of the vital objectives of health systems, as defined by the World Health Organization. However, no consensus has yet been reached on the measurement of CHE. With the aim of further relieving the adverse effects of CHE and alleviating the problem of illness-caused poverty, the Critical Illness Insurance (CII) program has been operational in China since 2012. In order to verify whether the different measurements of CHE matter under China's CII program, we compare the two-layer CII models built by using the basic approach and the ability-to-pay (ATP) approach at a range of thresholds. Exploiting the latest China family panel studies dataset, we demonstrate that the basic approach is more effective in relieving CHE for all insured households, while the ATP approach works better in reducing the severity of CHE in households facing it. These findings have meaningful implications for policymaking. The CII program should be promoted widely as a supplement to the current Social Basic Medical Insurance system. To improve the CII program's effectiveness, it should be based on the basic approach, and the threshold used to measure CHE should be determined by the goal pursued by the program.